ANALISIS PERANCANGAN DAN PENGEMBANGAN AGROSISTEM SAYURAN HIDROPONIK EMAK FARM AND HIDROPONICS, WARU, SIDOARJO - Ayunda Daratista; Indra Tjahaja Amir; Nisa Hafi Idhoh (Agros Journal of Agriculture Science, 2023)
This research was conducted on the hydroponic vegetable business "Emak Farm and Hidroponics" in Wadung Asri Village, Waru District, Sidoarjo Regency which aimed to analyze the design and development of agrosystems in the hydroponic vegetable business "Emak Farm and Hidroponics". The method used is the APPAS method, which is a learning method to find out the sides of the problem related to the case agrosystem that is used as the object of research. The number of respondents in this study was 28 people.  Data collection was taken by conducting interviews and distributing questionnaires. In this study, it was found that Emak Farm and Hydroponics has a major problem, namely production results that are not optimal. The main problem is caused by the non-optimal maintenance of vegetables, and the lack of a large number of workers working in this venture. To solve these problems, actions that need to be taken are pest and disease control using vegetable pesticides, attending hydroponic farming training, recruiting fresh graduate workers in agriculture.INTISARIPenelitian ini dilakukan pada usaha sayuran hidroponik “Emak Farm and Hidroponics” di Kelurahan Wadung Asri, Kecamatan Waru, Kabupaten Sidoarjo yang bertujuan untuk menganalisis perancangan dan pengembangan agrosistem pada usaha sayuran hidroponik “Emak Farm and Hidroponics”. Metode yang digunakan adalah metode APPAS, yang merupakan suatu metode pembelajaran untuk mengetahui sisi-sisi permasalahan terkait dengan agrosistem kasus yang dijadikan sebagai objek penelitian. Jumlah responden dalam penelitian ini sebanyak 28 orang.  Pengumpulan data diambil dengan melakukan wawancara dan penyebaran kuesioner. Pada penelitian ini didapatkan hasil bahwa Emak Farm and Hidroponics memiliki masalah utama yaitu hasil produksi yang tidak maksimal. Masalah utama disebabkan oleh pemeliharaan sayuran yang tidak optimal, dan kurangnya jumlah tenaga kerja yang bekerja dalam usaha ini. Untuk menyelesaikan masalah tersebut, tindakan yang perlu dilakukan adalah pengendalian hama dan penyakit menggunakan pestisida nabati, mengikuti pelatihan pertanian hidroponik, merekrut tenaga kerja fresh graduate di bidang pertanian.